New directions in hepatitis B therapy research - Lewandowska, Marta; Piekarska, Anna (Clinical and Experimental Hepatology, 2017)
Chronic hepatitis B treatment is available for a long period, allowing disease control and infection suppression, but it is rarely responsible for HBsAg clearance. None of the drugs available aim at cccDNA, the obstacle in HBV infection eradication. Complications related to CHB, such as liver insufficiency, cirrhosis, and hepatocellular carcinoma are reduced in conditions of good viremia suppression, but still exist even after HBsAg seroclearance, what makes a need for urgent forthcoming of new therapeutics. Recent years brought promising and interesting results of experimental approaches, which are directed against different phases of HBV life cycle, target ccc DNA, or boost, and restore host immune response. Unfortunately, encouraging results in vitro and on animal models are not always reflected in human. Nevertheless, the multiplicity of novel antivirals allows to expect that at least some of them will enter clinical practice and relieve patients from chronic hepatitis B, fatal and devastating disease.